INTERCONNECTED DC MICROGRID FOR EFFICIENT USE OF RENEWABLE ENERGY SOURCES - S.K. Kesri; P. Kumar (INTERNATIONAL JOURNAL ENGINEERING AND APPLIED TECHNOLOGY (IJEAT), 2019)
The use of a dc micro-grid with the interconnection of the main ac power supply, which is provided from renewable energy sources such as the sun, wind, and other sources, was investigated in this article. Micro-grids will play a significant role in the future development of the energy sector, but the generation phase may differ. In this article, we show that when we use green energy sources for dc applications such as smartphone chargers, laptop chargers, and LEDs, the performance of the dc micro-grid device improves by up to 40%. This is due to the reduction of ac to dc and back to ac, which results in excessive power conversion losses in the current system. The PIC16F73 microcontroller is used to power the micro-grid device and solar tracker, increasing the model's performance. When this sort of device is attached to a specific load, it uses more power during off-grid renewable generation, resulting in more pulse width modulation (PWM) waveform generation, demonstrating the system's failure compared to renewable energy sources.